Γ′ precipitates with a twin orientation relationship to their hosting grain in a γ-γ′ nickel-based superalloy. (August 2018) - Vernier, Suzanne; Franchet, Jean-Michel; Dumont, Christian; Vennéguès, Philippe; Bozzolo, Nathalie
Abstract: In a polycrystalline γ-γ′ nickel-based superalloy, γ′ precipitates with a close-to-twin orientation relationship to their surrounding matrix (named T-type precipitates) are found in recrystallized grains located near specific unrecrystallized grains (named recovered grains). This type of γ/γ′ interface has not been reported in literature before. Inherited from the ingot conversion process, recovered grains are characterized by a high density of micrometric and close-to-coherent γ′ precipitates. Resulting from the interaction of the recrystallization front with the latter precipitates, the T-type precipitates appear to form onto the recrystallization front. The present paper details the crystallographic characteristics of the T-type precipitates. Graphical abstract: Unlabelled Image